Comparative evaluation of duration of extraction space closure and degree of root resorption with conventional and self-Ligation brackets - Raj Kumar Maurya; Preeti Bhardwaj; Harpreet Singh; Harsh Ashok Mishra (Wolters Kluwer Medknow Publications, 2022)
Introduction: Determination of difference between conventional and passive self-ligating brackets (SLBs) in respect of extraction space closure, patient perception and root resorption. Material and Methods: Eighty patients were divided into four groups of 20 each with age-sex-matched control using a simple randomisation technique and allocation concealment with a closed opaque envelope method. Group 1 consisted of conventional brackets with Connecticut New Archwire (CNA) wire mushroom loop, group 2 consisted of conventional brackets with TAD (AbsoAnchor, Korea) supported retraction, group 3 consisted of passive SLB with CNA archwires (Libral Traders, India) mushroom loop and group 4 consisted of passive SLB brackets with TAD (AbsoAnchor, Korea) supported retraction. The rate of retraction, root resorption and patient satisfaction were assessed. All conventional brackets (Orthox, USA) and passive SLBs (CaptainOrtho, India) had 0.018 Roth prescriptions with a slot size of 0.018 × 0.025. Results: Retraction was the fastest in group 2 with a mean of 1.266 ± 0.14 mm/4 week and a duration of 23.40 weeks. Similarly, group 4 showed the most sluggish movement with a mean of 1.182 ± 0.80 mm/4 weeks with a total duration of 25 weeks; howeverdifferencesce among groups were not statistically significant (P = 0.470). Conclusion: SLBs have advantage of better patient comfort, less pain and reduced chairside time. Though the present study found increased treatment duration with SLB along with friction mechanics, refuting the previous claims of reduced friction with SLBs, however, the difference was not statistically significant and results have to be extrapolated with caution and experience considering other advantages of SLBs.